Potret pengetahuan bidan Puskesmas/Desa dalam mendeteksi status gizi buruk pasca sosialisasi GEMPITA ASA di Provinsi Aceh - Azhari Azhari; Abdul Hadi; Arnisam Arnisam (Jurnal SAGO Gizi dan Kesehatan, 2022)
Background: Midwives are the health professionals responsible for educating the public and recognizing nutritional issues in infants. The use of the MUAC scale is a straightforward and highly sensitive approach for detecting nutritional problems in toddlers. The use of the MUAC scale for toddlers is anticipated to provide an independent technique for detecting nutritional abnormalities in toddlers, particularly malnutrition.Objective: To describe the knowledge of midwives in Aceh Province on the detection of severely underweight and underweight using anthropometric indicators and the usage of the MUAC scale for toddlers.Method: This research is a cross-sectional examination of a program's effectiveness. This study's sample consisted of 553 community health center/village midwives from the Aceh province. The knowledge of midwives was assessed via a questionnaire administered following the "National Nutrition Day Webinar: Preventing child mortality through early detection of nutritional issues" presentation. Data processing begins with the processes of editing, coding, and cleansing. The analysis of data was performed univariately.Results: Results indicated that the community health center/village midwives' ability to diagnose growth abnormalities in children under the age of five fell into three categories: moderate (68.0%), good (14.1%), and very good (17.9%). In addition, more than 50% of community health center/village midwives are aware of the function of the MUAC scale (severely underweight if the MUAC < 11.5 cm), but more than 50% are unaware of the criterion for malnourished children (if they meet one of the criteria). Indicators, specifically WHZ index < -3 SD; MUAC < 11.5 cm, and the presence of edema.Conclusion: The midwives are more adept at identifying malnutrition and undernutrition in children under five than anthropometrists are at doing so.